STRUKTUR KAPITAL PADA PERUSAHAAN TRADE SERVICE AND INVESTMENT SEKTOR PERDAGANGAN BESAR DI BEI TAHUN 2017 - 2018 - Titis Nistia Sari; Dhea Zatira (Universitas Muhammadiyah Tangerang, 2019)
This study aims to look at the capital structure of the Trade Service and Investment companies in the large trade sector listed on the Indonesia Stock Exchange for the period 2017-2018. This study sample consisted of a sample of 42 financial statements of trade service companies and large trade sector investments. The method used in this study is the panel data regression method with the right model is the Random effect model. The results of this study can be concluded that the increase in company value is influenced by ROE (Return On Equity) and TATO (Total Asset Turn Over) on the capital structure. ROE variabel (Return On Equity) has a negative relationship and has a significant effect as expected. While the TATO variabel (Total Asset Turn Over) has a positive relationship and has a significant effect as expected. Keywords: Capital Structure, Profitabilitas and Activity